Permian foraminifers from the exotic limestone blocks within the central Qiangtang Metamorphic Belt, Tibet and their geological implications. (November 2022) - Ju, Qi; Zhang, Yi-chun; Yuan, Dong-xun; Qiao, Feng; Xu, Hai-peng; Zhang, Hua; Zheng, Quan-feng; Luo, Mao; Qie, Wen-kun; Zhai, Qing-guo; Zhang, Yu-jie; Shen, Shu-zhong
Highlights: The age of the exotic limestone blocks within the Central Qiangtang Metamorphic Belt is late Kungurian to Roadian. The exotic limestone blocks came from the Shuanghu type of Permian sequences in the South Qiangtang Block. A strong subduction and accretion process happened during the closure of the Longmu Co-Shuanghu Paleotethys Ocean. Abstract: The Central Qiangtang Metamorphic Belt (CQMB) is a subject of long-standing controversy for decades with respect to its origin and tectonic evolution. In this study, two foraminiferal faunas are reported from the exotic limestone blocks in the Jiaomuchaka and Jiangaizangbu sections within the CQMB. In total, 9 species of fusulines and 32 species of smaller foraminifers have been discovered in the Jiaomuchaka section, and 10 species of fusulines and 15 species of smaller foraminifers have been documented in the Jiangaizangbu section. In terms of the presence of the fusulines Pseudodoliolina ozawai, Presumatrina neoschwagerinoides, Neoschwagerina simplex and Afghanella sp., an age of late Kungurian to Roadian can be assigned to the faunas. A comparative study on the stratigraphic sequence and foraminiferal faunas between the exotic limestone blocks and contemporaneous deposits in the adjacent areas reveals that the exotic limestone blocks resemble strata of the Lugu Formation in the Shuanghu and Minzhuochaka areas in the South Qiangtang Block. The presence of these exotic limestone blocks within the CQMB suggests that the in-situ deposits of the Lugu Formation have been partly subducted beneath the North Qiangtang Block during the closing of the Paleotethys Ocean along the Longmu Co-Shuanghu Suture Zone.